Freedom of Opinion and Expression in the Second Period of President Joko Widodo: A Review of Jurgen Habermas' Deliberative Democracy - Toha, La Ilham (DIALEKTIKA, 2024)
This research explores the dynamics of freedom of opinion and expression during the second period of Joko Widodo's presidency using the lens of deliberative democracy according to the thinking of Jurgen Habermas. Through the method of philosophical descriptive hermeneutic analysis of Jurgen Habermas' deliberative democracy, as well as analysing the index of democracy and freedom of opinion and expression in the second period of Joko Widodo's presidency. This research aims to understand the extent to which the principles of deliberative democracy are reflected in government policies and public behaviour. The findings show that in the second term of President Jokowi's administration there was a decline in the democracy index due to the restriction of freedom of expression and opinion by using the ITE Law. This has resulted in people being afraid to express their opinions in public spaces. According to Jurgen Habermas' deliberative democracy in reviewing the second term of President Joko Widodo's administration, Indonesia's democratic governance system lacks inclusiveness, egalitarianism and dynamism in public decision-making, so this is a major obstacle on the way to true deliberative democracy. Therefore, the study concludes by suggesting the need for further reforms in strengthening democratic institutions and culture to enhance meaningful public participation and ensure broader and more inclusive freedom of opinion and expression.